2016
DOI: 10.1111/ddi.12474
|View full text |Cite
|
Sign up to set email alerts
|

Taking the heat: distinct vulnerability to thermal stress of central and threatened peripheral lineages of a marine macroalga

Abstract: Aim Although many studies have reported the effects of climate change on species' distributions, most of them consider each species as a physiologically homogenous unit. However, different lineages or populations inhabiting distinct bioregions within a species' distributional range can retain unique genetic diversity that could result in distinct adaptive capacities. A recent, large, climate‐correlated distributional range contraction occurred at the southern edge of the intertidal macroalga Fucus vesiculosus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…, Saada et al. ). Ecotypic divergence has been shown to lead to rapid speciation in several organisms including macroalgae (i.e., adaptation to low salinity in the Baltic sea in Fucus in the time span of a few hundreds of years, Pereyra et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…, Saada et al. ). Ecotypic divergence has been shown to lead to rapid speciation in several organisms including macroalgae (i.e., adaptation to low salinity in the Baltic sea in Fucus in the time span of a few hundreds of years, Pereyra et al.…”
Section: Discussionmentioning
confidence: 98%
“…Differences in sensitivity to UVB radiation were also detected between G. birdiae strains from CE and SP states (Ayres-Ostrock and . Physiological divergence between habitats, linked to distinct resilience capacity to temperature fluctuation and emersion (i.e., desiccation) stress, has been shown in other intertidal seaweeds, for example in the brown alga Fucus vesiculosus (Nicastro et al 2013, Saada et al 2016. Ecotypic divergence has been shown to lead to rapid speciation in several organisms including macroalgae (i.e., adaptation to low salinity in the Baltic sea in Fucus in the time span of a few hundreds of years, Pereyra et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophytes can be locally adapted to their thermal regime (e.g., Zardi et al, 2013;Pereira et al, 2015;Saada et al, 2016;King et al, in press). This means that migrations are rather the dislocation of those adapted subpopulations, and must also be investigated/modeled as such (as in Assis et al, 2016b).…”
Section: A1 Genetic Variation and Structure-explained By Biogeographimentioning
confidence: 99%
“…When such approaches were employed variation in thermal phenotype was still observed. In range centre to range edge transplants (cool to warm conditions), which simulate warming scenarios, studies either found that central populations could not tolerate range edge conditions (Gerard andDu Bois 1988, Bennett et al 2015) or performed poorer than local individuals (Saada et al 2016).…”
Section: Disentangling Plasticity From Adaptationmentioning
confidence: 99%
“…Locations where this threshold was exceeded during the Ningaloo Niño heatwave in 2011 (Feng et al 2013) experienced widespread population loss and shifts in community structure (Smale and Wernberg 2013). Similarly, Saada et al, (2016) concluded that intraspecific differences in thermal tolerances of the intertidal fucoid, Fucus vesiculosus, may render central populations along the Iberian Peninsula vulnerable to warming.…”
Section: Significance and Limitation Of Findingsmentioning
confidence: 99%